Effect of Aggregate and Binder Type on the Functional and Durability Parameters of Lightweight Repair Mortars - Martina Záleská (MDPI AG, 2021)
The subject matter of the work presented here is the development and evaluation of novel lightweight mortars that meet the functional and technical criteria imposed on repair mortars. In a broad experimental campaign, lime, natural hydraulic lime, and lime–cement mortars were designed and tested. Lightweight aggregate, expanded perlite, granules from expanded glass and zeolite were used as full replacements for quartz sand. The hardened mortars were tested at the ages of 28 days and 90 days. The conducted tests and analyses were focused on the assessment of structural, mechanical, hygric and thermal parameters. The salt crystallization resistance and effect of salt presence on the hygroscopicity of the investigated mortars were also investigated. The use of lightweight aggregates in the composition of mortars resulted in their high porosity, low density, satisfactory mechanical parameters, improved water vapor transmission capability and water absorption. The mortars with expanded perlite and glass granulate were ranked among thermal insulation mortars of classes T1 and T2, respectively. The use of lightweight aggregates enabled the development of mortars with great durability in terms of salt action, which was almost independent of binder type. The ability to accommodate water vapor was increased by the effect, i.e., the use of lightweight aggregates and the presence of salt in mortars increased porous space. Taking into account the compatibility, functional, and technical criteria, lime- and natural hydraulic lime-based lightweight mortarswere classified as repair mortars, providing improved thermal performance. The lime–cement lightweight plasters can be recommended only for repair of building structures where cement and lime–cement materials were original applied.